ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF TWO ENDEMIC PLANTS FROM AKSARAY IN TURKEY - Ozusaglam, Meltem Asan; Darilmaz, Derya Onal; Erzengin, Mahmut; Teksen, Mehtap; Erkul, Seher Karaman (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This study was designed to examine the in vitro antimicrobial and antioxidant activities of the methanol, ethanol, water, n-hexane and dicholoromethane extracts of two Allium species (Allium scabriflorum and Allium tchihatschewii) which are endemic for the flora of Turkey. The antimicrobial efficiency of the plant was evaluated according to disc diffusion and microdilution broth methods. The antimicrobial test results showed that the extracts of A. scabriflorum and A. tchihatschewii showed varying degrees of antimicrobial activity on the tested microorganisms. The extracts were screened for their possible antioxidant activities by three complementary tests; DPPH free radical-scavenging, scavenging of hydrogen peroxide and metal chelating activity assays. All the extracts of A. scabriflorum and A. tchihatschewii exhibited lower DPPH free radical scavenging activity but higher metal chelating activity when compared to standards. The values of scavenging of hydrogen peroxide of the extracts were higher than the standards that of α-tocopherol, BHA, BHT and trolox, but close to that of ascorbic acid. In addition to the antioxidant activity of these plants, the total phenolic compounds and flavonoids were also measured in the extracts. The results presented here may suggest that the extracts of A. scabriflorum and A. tchihatschewii possess antimicrobial and antioxidant properties, and therefore, they can be used as a natural preservative ingredient in food and/or pharmaceutical industry.